APPRENTICE TEACHERS BUILD STUDENTS' CREATIVITY THROUGH A JOYFUL STAGE AT PESANTREN DARUL AMANAH, KENDAL CENTRAL JAVA - Yuliangsih, Durrotul Hikmah; Hasanah, Fatmawati Nur (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2024)
This article aims to discuss teachers' role in improving students' creativity through the joyful stage event at Pesantren Darul Amanah in Kendal. The contribution of the research conducted is aimed at opening people's minds to the fact that service teachers in pesantren have a big role in creativity to improve the quality of students and pesantren. This research is a field research (field research) using descriptive qualitative research. The data obtained using structured interview techniques were then analyzed with descriptive analysis. The results of this study are the form of the teacher's role in increasing the creativity of the students through the joyful stage event at Pesantren Darul Amanah Kendal is through various coaching by the teachers by becoming the person in charge of the event, with the model of the students who assemble all the activities of the event then handed over to each person in charge of the teachers. If there are deficiencies, the teacher's role is also as a guide. The role of teachers in increasing creativity in the joyful stage event at Pesantren Darul Amanah Kendal has a positive impact, including mental training, expanding students' potential, awakening Islamic values, and training students to create entertaining and educational art performances.